MATH SOLVE

3 months ago

Q:
# Pablo simplified the expression(2^-4)^-2 as shown. (2^-4)^-2=2^-4*^-2=2^-8Which statement explains Pablo’s error?A. He should have added the exponents instead of multiplying them.B. He should have divided the exponents instead of multiplying them.C. He should have found 8 as the exponent, not –8.D. He should have written mc014-3.jpg as mc014-4.jpg.

Accepted Solution

A:

(2^-4)^-2 = 2^[(-4)*(-2)] = 2^8

answer

C. He should have found 8 as the exponent, not –8.

answer

C. He should have found 8 as the exponent, not –8.